Bottom-Up and Reciprocal Citizen Science: Untapped Resources of Novel Ideas. Preliminary Experiences of a Citizen Science As Public Engagement Program - Hargitai, Evelin Gabriella (2022)
In scientific research, citizen science is widely regarded as an involvement of the general public in scientific research initiated by universities, scientific organisations or research centres. In this top-down approach (top-down citizen science), participating citizens usually collect data or provide samples for research — that is, they are considered volunteer research assistants following instructions. This study analyses alternatives of top-down citizen science: one, widely known, which is the bottom-up way of citizen science and another, the reciprocal approach suggested by the authors. Bottom-up is based on local initiatives and is constituted by community-led projects. For bottom-up citizen science, scientific organisations may provide methodological and organisational frames. However, the idea and the implementation remain in the competence of the participant citizens. Reciprocal citizen science emerged from a need for a more holistic policy toward citizen science. As part of this, identifying viable citizen-initiated projects, measuring their scientific and/or innovation potential, and integrating them into a citizen science mentor program are questions to be systematically discussed and solved. This study addresses methodological challenges in mentoring citizen science projects, covering a mentor training concept for citizen science designed by the Institute of Transdisciplinary Discoveries. Encouraging citizen research is needed for a new impetus to scientific discoveries. The perspectives of people with no scientific background can also advance problems — mainly those that require fresh and unbiased approaches. Citizen science may also be a solution for leveraging the knowledge of science leavers.